The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2002
DOI: 10.1007/s00520-002-0360-5
|View full text |Cite
|
Sign up to set email alerts
|

Creating a language for 'spiritual pain' through research: a beginning

Abstract: The findings presented in this discussion seek to make a contribution to fostering an appreciation of the importance of research on spirituality, a previously neglected dimension of health care. Qualitative research methodology based on open-ended interviews with 12 survivors of haematological malignancies was used. The interviews were transcribed verbatim and thematically analysed using the NUD*IST computer package. The preliminary findings from the study indicate a need for the development of a new language … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 21 publications
1
62
0
1
Order By: Relevance
“…It seems that existential suffering comes in many ways for these patients. In the literature there is currently no standard definition of existential pain, but generally, existential pain has been used as a metaphor for suffering (Saunders, 1988;McGrath, 2002McGrath, , 2003Musi, 2003;Strang et al, 2004). Strang et al (2004) concluded that it is obvious that existential pain is not a uniformly defined entity, as it obviously can be understood both as existential suffering and/or pain expressed in physical terms.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that existential suffering comes in many ways for these patients. In the literature there is currently no standard definition of existential pain, but generally, existential pain has been used as a metaphor for suffering (Saunders, 1988;McGrath, 2002McGrath, , 2003Musi, 2003;Strang et al, 2004). Strang et al (2004) concluded that it is obvious that existential pain is not a uniformly defined entity, as it obviously can be understood both as existential suffering and/or pain expressed in physical terms.…”
Section: Discussionmentioning
confidence: 99%
“…Spirituality embodies a sense of connectedness to a personal god or higher force or power, and is considered a broader construct than religion. 28,29 Some initial contemporary efforts have been made to define spirituality from the perspective of dying patients. Chao and colleagues asked six Buddhist and Christian terminally ill cancer patients in Taiwan what the essence of spirituality was to them.…”
Section: Spirituality and Existentialismmentioning
confidence: 99%
“…The problem is that family and friends perceive the medical drama to be over at a time when many patients are only starting to deal with the emotional and spiritual consequences. Although the full findings on this issues are published elsewhere (McGrath, 2002b;2003a), an indication of the problem can be seen in the following statement:…”
Section: It Hurts When People Don't Listenmentioning
confidence: 99%
“…Such a connection can be threatened by a break with the normal or expected relationships and dissatisfaction with life through physical, identity, relational, and existential losses (McGrath, 2003a). When the disconnection is acutely painful (a subjective phenomenon depending on the individual), it is then experienced as 'spiritual pain', creating a void that challenges the individual's ability to make meaning from his or her existence (McGrath 2002b). If the 'spiritual pain' is sufficiently severe, it can lead to suicidal ideation.…”
Section: Introductionmentioning
confidence: 99%